Artificial Immune System (AIS) application for maximum loadability determination / Mohd Noramar Mohd Munawar - Mohd Munawar, Mohd Noramar (2005)
This project report presents the Artificial Immune System (AIS) application to determine the maximum loadability. This project determines the maximum loadability at the PQ buses in a power system. The technique presented here generates exact estimates of the maximum possible amount of load increase that the system can tolerate along a specific path, as well as the corresponding voltage vector. The proposed technique was tested on the IEEE 30 bus Realibility Test System (RTS) and the result proved that the proposed technique is able to estimates the maximum loadability in a system.